Morphological and Molecular study of Seven New Recorded of Ostracod in - Kurdistan Region, Iraq - Berivan A. Latef; Luay A. Ali (Maǧallaẗ al-baṣraẗ al-ʻulūm al-zirāʻiyyaẗ)
The current study conducted the first characterization of morphological and molecular of seven Ostracoda species new to Iraqi fauna which are; Heterocypris salina, H. spadix, Dolerocypris sinensis, Cyprinotus unoi, Eucypris virens, Sclerocypris exserta and Notodromas monacha that belongs to two families (Cyprididae and Notodromatidadae) collected from 17 different sites which are stream, lakes and rivers in the boundary of Province, from September 2021 to October 2022. For biological purposes, samples of aquatic shore plants (Cynodon dactylon, Polygonum sp., Nerium oleander and Nasturtium officinale), algal municipal (Anabaena and Chlorella vulgaris), were also collected zooplanktonic net was used in the sampling mesh-size (55 μm pore size).Samples placed in an oxygen instrument for about one week after being transformed into the laboratory to allow the ostracod species to grow. After the maturation period, adult species were fixed (were preserved) in 70% and 100% ethanol for morphological and molecular analysis respectively. PCR product of COI was sequenced using forward primer COI F 5'(ACCCGCTGAATTTAAGCAT)3' and reverse primer COIR 5'( CTCTTCAGATACTTTTCAAC) 3' then registered  in the GenBank database with their accession numbers. The phylogenetic tree was constructed; the studied species were recognized (as new records to the Iraqi fauna of ostracods) and described from Iraq for the first time. The goal of present study is the molecular study the species besides the phenotypic identification for more accurate taxonomic results.